2019
DOI: 10.1115/1.4043251
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Stall and Surge in Low-Speed Contra-Rotating Fans

Abstract: This paper reports on a theory for poststall transients in contra-rotating fans, which is developed from the basic Moore–Greitzer theory. A second-order hysteresis term is assumed for the fan pressure rise, which gives the theory more capabilities in predicting the fan instabilities. The effect of the rotational speed ratio of the two counter rotating rotors on the fan performance during the occurrence of surge and rotating stall are studied (the rotational speed of the front rotor is assumed to be kept consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In summary, to solve the overload problem, we adopted the traditional method with different loads (e.g., by reducing the load) or raised the power margin for R2. (25)(26)(27)(28) By comparing our proposed method of AVS control with traditional methods, we observed that our novel method is more comprehensive and has higher performance.…”
Section: Results and Verificationmentioning
confidence: 93%
See 1 more Smart Citation
“…In summary, to solve the overload problem, we adopted the traditional method with different loads (e.g., by reducing the load) or raised the power margin for R2. (25)(26)(27)(28) By comparing our proposed method of AVS control with traditional methods, we observed that our novel method is more comprehensive and has higher performance.…”
Section: Results and Verificationmentioning
confidence: 93%
“…(20)(21)(22)(23)(24) To solve the overload problem encountered in R2 under small-flow conditions, a common solution is to adopt different loads (e.g., by reducing the load) or raise the power margin for R2. (25)(26)(27)(28) Nevertheless, these measures usually reduce the overall performance for other flow conditions. Some studies showed that adaptively changing the load distribution by adjusting the impeller velocity of the rotor may effectively and optimally enhance the overall performance for all flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent work done by Khaleghi et al (2020) and Shahriyari et al (2019), the compressor pressure rise function which was used by Moore (1984a) and Moore and Greitzer (1986) was modified to include a second order derivative term, which enabled the investigation of the stall cell transient behavior. The same hypothesized function is used in the current study:…”
Section: Fig 1 Compressor Axisymmetric Characteristicmentioning
confidence: 99%
“…By measuring and comparing the flow characteristics and unsteady characteristics of the three sets of CRFs, they concluded that, under the condition of keeping the rotor angular velocity of two stages approximately equal, redistributing the load of the FR to 60% and the RR to 40% could reduce the loss of the RR. Shahriyari et al [9] reported a CRF post-stall transient theory, which could better predict the instability of a CRF. Besides, by studying the effect of different rotating speeds between rotors, which matched the stall and surge pattern, they concluded that, the higher the RR speed, the stronger the fan resistance to a surge caused by throttling.…”
Section: Introductionmentioning
confidence: 99%